A Legal Review of Islamic Law on The Issue of A Child’s Origins And The Legal Certainty of A Child’s Status Under Law No. 16 of 2019 - Ahmad Nafhani; Gusti Fadhil Fithrian Luthfan; Riza Puspita Sari; Yulianiva Maulida; Rizky Dwi Utami; Ari Ekawie Baskhoro (Fakultas Syariah UIN Antasari, 2026)
This study examines the issue of child lineage and legal certainty of child status from the perspective of Islamic law and its relevance to Law No. 16 of 2019 on Marriage. Disputes over child origins often create complex legal and social consequences, particularly regarding lineage (nasab), inheritance rights, and parent–child obligations. Islamic law strictly links lineage to a valid marriage in order to preserve the integrity of descent and ensure legal certainty. However, social realities present cases beyond this ideal, including children born outside marriage, unregistered marriages, and unclear parentage.Law No. 16 of 2019 seeks to provide legal certainty through mechanisms such as child recognition, legitimation, and protection. This research applies a normative juridical method with a comparative approach to analyze differences and potential harmonization between Islamic law and positive law. The study focuses on the concept of nasab, its legal implications, and the extent to which the law provides comprehensive solutions.The findings indicate that while Islamic law and positive law share the objective of protecting children, differences in determining lineage create challenges for legal certainty. Harmonization is therefore necessary to ensure both justice and the protection of children’s rights.